THE NEW HOPE OF UZBEKISTAN FOOTBALL - ABDUKODIR KHUSANOV AND HIS WAYS OF SUCCESS (International journal of artificial intelligence, 2024)
This article explores the journey of Abdukodir Khusanov, who is introducing Uzbekistan's football to the world, particularly Europe. It examines his entry into the world of football, his achievements, successes, and significant role in the development of Uzbek football. Additionally, it highlights the key factors behind his success on the international stage through his playing technique.